Persian books of Munshi Naval Kishor’s publisher house which are stored in the National and Science Library of Kazakhstan - Кaмбaрбековa Г. A. (Journal of Oriental Studies, 2017)
This paper devoted to the Persian Printed books of well-known Indian publisher Munshi Nawal Kishor (1836-1895) which were published in Kanpur and Lakhnow. Most of the Persian Printed books were published in India, particularly in Munshi Nawal Kishor’s publisher house. Persian Printed books spread all over the India, even abroad India. Especially, many Persian Printed books of Munshi Nawal Kishor’s publisher house were used in maktabs and madrasas of Central Asia. Persian Printed books of Munshi Nawal Kishor’s publisher house preserved in the fund of National and Science Library of Kazakhstan considered as confirmation materials. In this paper Munshi Nawal Kishor considered as a person who contributed in the development of education system of Central Asia with exact samples.